A Study on the Factors Influencing Coal Fracturing Range Caused by Liquid Carbon Dioxide Phase Transition. (24th May 2022) - Hu, Xinyu; Zhang, Runxu; Zhang, Bailin; Zhang, Xinghua; Zhang, Lulu; Yang, Yongdan; Yan, Fazhi
Abstract : Liquid carbon dioxide phase transition fracturing technology (LCPTF) is an effective method to increase coal seam permeability, but there are many factors that affect the fracturing effect. Blasting pressure, vent diameter, and blasting time are important factors that affect the fracturing effect. However, very limited studies were performed in this regard. Therefore, in this paper, a multifield coupled model for fracturing coal bodies by LCPTF is established; the effect of blasting pressure, vent diameter, and blasting time on blasting effectiveness was studied; a numerical simulation study based on the seepage field and stress field is performed and verified in the field based on the specific geological conditions of Hujiahe mine. Experimental results show that the fracturing radius and the maximum displacement of coal increase with the increase of blasting pressure, and the fracturing radius is 4.875 m when the blasting pressure is 280 MPa, which is 9.6% higher than that of 200 MPa, and the effect is obvious. The fracturing effect improves with the increase of vent diameter but the effect is modest. In general, the fracturing effect increases with the increase of CO2 impact duration, and when there is no gas impact, the fracturing radius basically remains the same. The maximum displacement gradually decreases with time, and its maximum displacement of the coal body decreases by 33.69% at 200 s. After field blasting, the gas flow attenuation coefficient was reduced by up to 85.7% and the effective radius of influence was between 4 and 5 m.